1989
DOI: 10.1007/bf01537261
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal survey of self-reported bowel habits in the United States

Abstract: Information concerning bowel habits was gathered from a representative sample of 14,407 United States adults in the first National Health and Nutrition Examination Survey in 1971-1975 and approximately 10 years later among the same individuals. The prevalence of self-reported constipation, diarrhea, infrequent defecation (three or fewer bowel movements per week), and frequent defecation (two or more bowel movements per day) increased with aging. Women were more likely than men (P less than 0.05) to report cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
203
11
10

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(242 citation statements)
references
References 12 publications
18
203
11
10
Order By: Relevance
“…These null associations may be due to the large proportions of women without habits of smoking (94%) or alcohol drinking (78%) and with a normal BMI (78%). Physical activity has also been associated with constipation in several studies (Everhart et al, 1989;Sandler et al, 1990;Dukas et al, 2003;Sanjoaquin et al, 2004); we, however, did not find the association. This may be because of our relatively rough assessment of physical activity because we classified the subjects only into two groups according to the frequency of participating sports club activities without consideration of other kinds of activities.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…These null associations may be due to the large proportions of women without habits of smoking (94%) or alcohol drinking (78%) and with a normal BMI (78%). Physical activity has also been associated with constipation in several studies (Everhart et al, 1989;Sandler et al, 1990;Dukas et al, 2003;Sanjoaquin et al, 2004); we, however, did not find the association. This may be because of our relatively rough assessment of physical activity because we classified the subjects only into two groups according to the frequency of participating sports club activities without consideration of other kinds of activities.…”
Section: Discussioncontrasting
confidence: 98%
“…The effect of dietary fiber on constipation is widely accepted, but only a few studies have found an inverse association between dietary fiber and constipation (Dukas et al, 2003;Sanjoaquin et al, 2004), and many other studies have failed to find this association (Everhart et al, 1989;Whitehead et al, 1989;Campbell et al, 1993;Towers et al, 1994). Unexpectedly, there seemed to be a positive association between dietary fiber intake and constipation in the Diet and constipation in Japanese women K Murakami et al present study, although the association disappeared after further adjustment for rice intake, suggesting that the association is largely due to an inverse association between rice intake and constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, constipation tends to affect a greater proportion of women concomitant with aging (Everhart et al 1989;Heaton et al 1992;Nakaji et al 2002bNakaji et al , 2004. Many women experience changes in their bowel habits at their menstrual cycle; most women report hard stools and prolongation of transit time during the luteal phase and loose and more frequent stools at the time of menses (Rees and Rhodes 1976;Wald et al 1981;Davies et al 1986;Whitehead et al 1988;Hinds et al 1989;Davies et al 1993;Celik et al 2001), though a few researchers did not find such differences (Wyman et al 1978;Turnbull et al 1989).…”
Section: Classification Into Groupsmentioning
confidence: 99%
“…Assessment of bowel habit is retrospective in nature and it is best done by questionnaire technique. [4][5][6][7][8] Normal bowel frequency is 3 to 21 motions per week. 9 Bowel movement is easy to assess but it is a poor guide of colonic function.…”
mentioning
confidence: 99%